Excellent outcomes for adolescents and adults with acute lymphoblastic leukemia and lymphoma without allogeneic stem cell transplant: the FRALLE-93 pediatric protocol. Issue 12 (December 2014) - Hocking, Jay; Schwarer, Anthony P.; Gasiorowski, Robin; Patil, Sush; Avery, Sharon; Gibson, John; Iland, Harry; Ho, P. Joy; Joshua, Douglas; Muirhead, Jenny; Lai, Hock; Irving, Ian
Abstract Adolescents and adults with acute lymphoblastic leukemia/lymphoma (ALL) have better outcomes when treated using pediatric protocols compared with treatment using adult protocols. We reviewed the progress and outcomes of 40 adolescents and adults up to 45 years of age, from three Australian centers, treated on the intensive French group for childhood ALL (FRALLE)-93 pediatric protocol. All except one patient achieved a morphologic complete remission following induction chemotherapy. Three-year overall survival for all-risk and standard-risk disease was 70% and 75%, respectively. The treatment protocol was generally well tolerated with no treatment related mortality. The FRALLE-93 pediatric protocol showed excellent overall survival for patients with standard-risk disease, without the need for allogeneic hematopoietic stem cell transplant in first remission.